Optimization of Implementation Costs at Margatiga Dam with Inundation Area Parameters Case Study: Margatiga Dam Project, Lampung - Andrew Agung W; Mahendra Andiek Maulana (Journal of Social Research, 2023)
Margatiga Dam is located at Lampung Province. The potential of high land acquisition cost may affect the total construction cost of the dam. A simulation needs to be conducted to calculate the volume of the dam reservoir with optimum reliability and benefit value. Calculation of the dam reservoir uses the storage capacity curve based on topographic map to derive the size area and reservoir volume on each elevation, a simulation is done afterwards to obtain the exact elevation of the optimum volume of reservoir. Simulation is conducted with three elevation alternatives; the spillway crest’s initial elevation of +22m, the raised elevation of +22,5m, and the lowered elevation of +21m. It can be concluded from the evaluation that spillway crest’s elevation with most benefit value is at an elevation of +22m with the reservoir reliability of 99,64%, BCR of 1,63, and the IRR of 13,34% with the total cost of Rp1.929.918.493.283.